Apontamentos sobre a Inserção do Brasil na Ofensiva Neoconservadora Internacional sob Bolsonaro: Notes on the Insertion of Brazil in the International Neoconservative Offensive under Bolsonaro - Rodrigues, Marlene Teixeira (Argumentum, 2024)
This article addresses the neoconservative offensive the neoconservative offensive in Brazil, from its articulation with the international extreme right, emphasizing how this agenda materializes through social policies and the centrality given to the family. Based on documentary research, the important articulation with international organizations was observed – with emphasis on the “transatlantic” Political Network for Values – and its repercussions on the agenda and initiatives implemented. Under the justification of acting in defense of "life from conception", "fundamental freedoms - of conscience and religion" and the so-called "natural family" - and the rights attributed to it, experiences are shared and gain concreteness in the government , in social policy and in different areas. An important part of this offensive is to dismantle public social policies and rights - especially the sexual and reproductive rights of women and LGBTQIA people, in the context of the war against the so-called “gender ideology” and “state interventionism”.